Neotropical Ablabesmyia Johannsen (Diptera: Chironomidae, Tanypodinae)–Part I - de Oliveira, Caroline Silva Neubern; Da Silva, Mário Antonio Navarro; Gessner, Alaíde Aparecida Fonseca (Zootaxa, 2013)
This is a series of three manuscripts about the genus Ablabesmyia. In the first new species are described, three species are re-examined and keys to males, pupae and larvae of known neotropical species are provided and an emended generic diagnosis of Ablabesmyia is given. The second manuscript will analyze the molecular data of Neotropical species and the third one will check, through a phylogenetic analysis, the truth of subgenera. In this study, twenty-four new species of Ablabesmyia Johannsen are described and figured: A. arquata, A. cauame, A. commata, A. communiba, A. cordeiroi, A, depaulai, A. diversa, A. ducke, A. fazzari, A. fusariae, A. gessnerae, A. gigas, A. jaquirana, A. laurindoi, A. manauara, A. martha, A. novema, A. parannulata, A. parareissi, A. pinhoi, A. rafaeli, A. separata, A. strixinoae and A. suiamissu. We re-examined A. cinctipes (Johannsen), A. infumata (Edwards) and A. metica Roback. The species were collected in Brazil, in lentic systems. Keys to males, pupae and larvae of known neotropical species of the genus Ablabesmyia are provided and an emended generic diagnosis of Ablabesmyia is given.